Glucose oxidase bioelectrodes in devices implanted in living plants for energy applications. (November 2019) - Galindo-de-la-Rosa, J.; Hernández-Torres, A.; Araiza-Ramírez, M.G.; Arriaga, L.G.; Ledesma-García, J.
Abstract: The growth of the world population and the lack of energy supply have led to the development of technologies to obtain alternative energy that has a minimal environmental impact, as is the case of fuel cells. In this work, the development of electrodes using glucose oxidase enzyme immobilized with functionalized carbon nanofibers on graphite rods is proposed for its application in a fuel cell implanted in living plants, specifically in cacti. The purpose is to convert solar energy to chemical and then, to electric energy, carrying out the glucose oxidation contained in these plants. The use of a living plant as a fuel cell comes from the idea of taking advantage of more efficiently the conversion of chemical energy, which comes from the plant's photosynthesis until is converted into electrical energy.